2019
DOI: 10.29333/ejosdr/5957
|View full text |Cite
|
Sign up to set email alerts
|

Wasteland Utilization for <i>B. balcooa</i> Cultivation: Socio-economic and Environmental Impacts through Bamboo-based Product Development

Abstract: Declining fossil fuel and increasing CO2 emissions from non-renewable fuel leading us to climate change which signifies to reduce fossil fuel dependency and promotes bioenergy as renewable. To address such issue Abellon Clean Energy has developed captive farming of B. balcooa for environment friendly bio-energy feedstock cultivation in; 1112, 2223, 2964 and 6175 plants/hectare densities to understand cost of cultivation and its subsequent use in cottage industry, energy substitute and high value products. Farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…On the other hand, CSB which were carbonized at the temperature range 350-400 ºC attained the volatile matter between 50.17-24.82% [25]. Another study showed that the CSB has obtained volatile matter of 36.47% at 350 ºC as well [26]. NaOH used during the biochar acid-base modification process also contributed to the discharge of volatile matter due to the organic matter decomposition in the biochar [24].…”
Section: Experimental Design and Optimization Of Adsorption Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, CSB which were carbonized at the temperature range 350-400 ºC attained the volatile matter between 50.17-24.82% [25]. Another study showed that the CSB has obtained volatile matter of 36.47% at 350 ºC as well [26]. NaOH used during the biochar acid-base modification process also contributed to the discharge of volatile matter due to the organic matter decomposition in the biochar [24].…”
Section: Experimental Design and Optimization Of Adsorption Efficiencymentioning
confidence: 99%
“…The addition of NaOH instigated an increment in the development of pores through an intercalation effect caused by the interaction of Na atom with the carbons in the biochar [29]. Base modification using NaOH and KOH can enhance the surface basicity and the amount of O-containing functional groups [26]. Whereas, the addition of HCl assists in removing the excess impregnating NaOH on the biochar surface and increasing surface acidity which generates more acidic functional groups to enable strong interactions between the modified biochars and heavy metal later [22,26].…”
Section: Figure 1 Sem Images Of (A) Raw Cs (B) Csb 2000x and (C) MCmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass is a promising eco‐friendly alternative source of renewable energy 2–5 in the context of current energy scenarios. It is also regarded as being both CO 2 ‐neutral and multifaceted in its application 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass is considered one of the main renewable energy resources of the future due to its large potential, economic viability and various social and environmental benefits. 1,2 Biomass absorbs carbon dioxide during growth, and emits it during combustion. Therefore, biomass helps the atmospheric carbon dioxide recycling and does not contribute to the greenhouse effect.…”
Section: Introduction *mentioning
confidence: 99%